The Fictions of Satire - Paulson, Ronald (Johns Hopkins University Press, 2019)
Originally published in 1967. In this study of the English Augustan satirists, and the Roman and subsequent authors who were their models, Professor Paulson shows how rhetoric relates to imitation, persuasion to presentation, and the imitation of the satirist to the imitation of the satiric object. He illustrates the tendency of the satirist to invade his own fiction and imitate not the prime object of his satire but the satiric persona, which consequently takes on a life of its own. By analyzing the satiric fictions of the precursors of the Augustans, the author reveals the elements they bequeathed to those who rode the high crest of the satiric wave in England, before the art of satire became submerged in the deepening trough of sentimental romanticism.Paulson shows the Tories Dryden, Pope, and Swift and the Whigs Addison and Steele to be the heirs of a long line of satirists ancient and modern, from Horace, Juvenal, Lucian, Apuleius, and Petronius to Rabelais, Cervantes and the English Elizabethan and Civil War poets. Taking Swift as his main example, Paulson examines the dualism of satire in its most interesting and ambiguous modes, and as the embodiment of rhetorical devices that are as complex mimetically as they are rhetorically.